Urban Street Pollutants - POLETO, Cristiano; MERTEN, GUSTAVO HENRIQUE (Pesquisas em Geociências, 2008)
The sediments carried by runoff water are an important part of this process because their presence in the bodies of water not only cause sedimentation problems but, mainly, they contaminate the water due to the presence of the pollutants found associated with sediments. The urban subwatershed under study is located in the metropolitan region of Porto Alegre city, Brazil. This paper aims to present the relation between pollutants on the street sediments and in suspended sediment sampled in the river. The collections of suspended sediment samples begun in the end of 2003 and finished in the end of 2006. Collections of urban dust samples (47 samples per km²) were taken in the main diffuse sources of the urban environment, represented by paved and non-paved streets, beyond the area with remaining vegetation, in some points of the bed river and in its margins. During these analyses, it was studied 29 samples of fluvial suspended sediments. The elements selected for this study are some of the most frequently found in high concentrations in urban areas (Zn, Pb and Cu). The results suggest it is occurring a high enrichment of the local sediment with these metals. The concentrations of these elements vary temporally during storms due the input of road runoff containing elevated concentrations of elements associated with vehicular traffic and other anthropogenic activities. In general, they have their most concentrations on the streets but they are carried to the channel during the storms.